Fluxos, encontros e dispersões : agenciamentos entre arte e clínica - Cavallini, Flávia de Macedo (2016)
We aim to mapping the artistic streams that peopled CAPS to care for the use of alcohol and other drugs in a city of the Espírito Santo between the years 2006 and 2016 and, with them, outline a collective landscape, relating them to some moments of art and the clinic from the nineteenth century to the present day. This relationship, in turn, aims to point out, albeit limited way, the mental health policy which is made tangentially art over the years, highlighting the madhouse forces that are still present, as well as the resistances that are created to address them. It highlights some moments of expansion of the clinic and its assemblages with modern and contemporary art, with the construction and regulation of artistic workshops in mental health services, seeking to make visible emerging streams that point, turn to a need for art deinstitutionalization, as well as the territorial other ways.